Primary Squamous Cell Carcinoma of Lung Leading to Metastatic Jaw Tumor - Chintamaneni Raja Lakshmi; M. Sudhakara Rao; Sujana Mulk Bhavana; Sivan Sathish (Case Reports in Pulmonology)
Metastatic tumors to the orofacial region are unusual and they may occur in the oral soft tissues or jaw bones. Owing to their clinical variability the diagnosis of such tumors is often a dilemma. We report a unique case of mandibular metastasis which became the first evidence of an occult primary in the lung.